The Role of Intestinal Flora in the Regulation of Bone Homeostasis - Li, Chengxiang; Pi, Guofu; Li, Feng (Frontiers in Cellular and Infection Microbiology, 2021)
Intestinal flora located within the intestinal tract comprises a large number of cells, which is referred to as the second gene pool of the human body and form a complex symbiotic relationship with the host. The knowledge of the complex interaction between intestinal flora and various life activities of host is a novel and rapidly expanding field. Recently, many studies are being conducted on the relationship between intestinal flora and bone homeostasis and indicate that intestinal flora can regulate bone homeostasis via the host immune, metabolic and endocrine systems. What’s more, based on several clinical and preclinical evidence, changing the composition and function of host intestinal flora through the application of probiotics, prebiotics and fecal microbiota transplantation is being considered to be a potential novel target for the regulation of bone homeostasis. Here, we searched relevant literature and reviewed the role of intestinal flora in the regulation of bone homeostasis and its modulating interventions.